The Influence of Service Marketing Mix Strategy on Decisions of Students in High School of Economic Sciences Pancasetia Banjarmasin - Apippudin Adnan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of marketing service mix strategy on student decisions in choosing a lecture at the Pancasetia School of Economics Banjarmasin. The number of samples of this study is 123 new undergraduate students S1 in 2017 and used sampling technique with Proportionate Stratified Random Sampling Method, using a questionnaire with Likert scale measurement unit. This type of research is descriptive quantitative. The nature of this research is to get an idea of a situation and problem and interpret it. The result of F test of simultaneous test of = 7.016 is greater than F table value of = 3.27, which indicates that product, price, place, promotion, physical evidence, people and process variables significantly influence student's decision in choose a lecture at the School College of Economics Pancasetia Banjarmasin. Partially value of significance price = 0.379, place = 0.301, promotion = 0.721, physical evidence = 0.366, and people = 0.264 which value is bigger than level of real = 0.05, meaning "price, place, promotion, physical evidence and people have no significant effect on the decision of college student in STIEPAN Banjarmasin ". While the most dominant variable affect the dependent variable is the product variable with the largest beta value = 0.361 with a significant level of = 0.001.